Influence of Strategic Supply Chain Management Practices on Performance of Cereal Businesses in Dagahaley Camp Market, Kenya - Muthoni, Komu; Mburu, David (International Journal of Supply Chain Management, 2022)
Purpose: The cereal supply chain within the wholesale and retail trade has been recognized to be below the market demand expectations. The cereals supply chain in Kenya has been dealing with serious issues of poor supplier management for a long time, with instances of malpractice reported, owing to distrust and commitment in the relationship, which has influenced the performance of cereal businesses. With this in focus, this research study was conducted to analyze the Influence of Strategic supply chain management Practices on Performance of Cereal businesses in Dagahaley camp market, Kenya. Methodology: A descriptive research design was adopted to assist achieve the study's objectives. The study sample size was 111 registered traders engaged in Distribution, retail and wholesale cereals trade from the Dagahaley market. A self-administered questionnaire was used to collect primary data. Data was analyzed using Statistical Package for Social Sciences (SPSS) version 20. Textual analysis was used to analyze qualitative data, while quantitative data was analyzed using descriptive statistics. Cronbach alpha test with a coefficient of 0.7 was used to ascertain and test the reliability of the data collection instrument. Results: The results indicated that Supply chain structure, Inventory control policy, and environment uncertainty had a positive and statistically significant effect on performance of cereals supply chain in Dagahaley market, directly affecting the performance of the cereals Businesses in Dagahaley market. Unique Contribution to Theory, Practice and Policy: The study therefore recommends that cereal businesses should continually implement the inventory control policies established in Dagahaley Market in order to cushion against excess/stock outs.